2022
DOI: 10.1155/2022/8115474
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Pan-Cancer Analysis Identifies CDK1 as an Immunological and Prognostic Biomarker

Abstract: Cyclin-dependent kinase 1 (CDK1) plays an important role in cancer development, progression, and the overall process of tumorigenesis. However, no pan-cancer analysis has been reported for CDK1, and the predictive role of CDK1 in immune checkpoint inhibitors (ICIs) therapy response remains unexplored. Thus, in this study, we first investigated the potential oncogenic role of CDK1 in 33 tumors by multidimensional bioinformatics analysis based on The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…On the other hand, cyclin‐dependent kinases (CDKs) are significantly upregulated in multiple types of cancer and their prognosis (Shen et al., 2019; Yang et al., 2022; Zhu et al., 2021). Specially CDK1 is instrumental in variable cell cycle phases and has been widely associated with and is significantly upregulated in HCC (Wu et al., 2018; Ye et al., 2021; Zhao et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, cyclin‐dependent kinases (CDKs) are significantly upregulated in multiple types of cancer and their prognosis (Shen et al., 2019; Yang et al., 2022; Zhu et al., 2021). Specially CDK1 is instrumental in variable cell cycle phases and has been widely associated with and is significantly upregulated in HCC (Wu et al., 2018; Ye et al., 2021; Zhao et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…40 It was also identified as an immunological and prognostic biomarker in multiple cancers. 41 These seven genes have been identified to induce or inhibit cell senescence in diverse cancers. 13,40,[42][43][44][45][46] However, until now, the functional roles of CDK1 in OSCC remain underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Our results of single-cell RNA sequencing analyses and clustering showed that T prolif cells had the highest T cell proliferation scores based on the expression levels of TRPGs among ten types of immune cells. In the original study, most of these TPRGs have been demonstrated to increase the proliferation cancer analysis shows that oncogene CDK1 is an immunological and prognostic biomarker, which may influence tumor immunity mainly by mediating the migration of immune cells to TME, and is positively associated with tumor mutational burden and microsatellite instability (54). CXCL12 is highly enriched in fibroblasts (16).…”
Section: Discussionmentioning
confidence: 99%
“…For example, TPRGs CDK1 and CXCL12 are expressed in both T cells and various cancer cells. A systematic pan-cancer analysis shows that oncogene CDK1 is an immunological and prognostic biomarker, which may influence tumor immunity mainly by mediating the migration of immune cells to TME, and is positively associated with tumor mutational burden and microsatellite instability ( 54 ). CXCL12 is highly enriched in fibroblasts ( 16 ).…”
Section: Discussionmentioning
confidence: 99%